School improvement in practice schools make a difference project (Falmer Press, 1996)
Following the demise of ILEA, Hammersmith and Fulham took responsibility for its schools in April 1990. Shortly afterwards the new administration agreed, as part of an overall attempt to raise standards, to implement the 'Schools Make a Difference' (SMAD) project. The project was the first of its kind in the country - an attempt by an LEA in partnership with all its secondary schools to implement a school improvement project backed by appropriate resources